Enhancing Cooperative Performance Through Innovation: Role of Entrepreneurial Orientation and Knowledge-Sharing Behaviour - Firdaus, Mukhammad Yusuf Naufal; Rofiaty, Rofiaty; Susilowati, Christin (Profit: Jurnal Adminsitrasi Bisnis, 2026)
This study examined the determinants of performance in consumer cooperatives in Pasuruan Regency, focusing on entrepreneurial orientation (EO), knowledge-sharing behaviour (KSB), and cooperative performance, with innovation as a mediating mechanism. A cross-sectional survey was conducted among 77 cooperatives, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings indicate that EO exerts a significant positive effect on both innovation and cooperative performance, whereas KSB influences performance only indirectly through innovation. Innovation thus fully mediates the relationships between EO, KSB, and performance, underscoring its strategic role in transforming internal resources into tangible organisational outcomes. These results corroborate the Resource-Based View (RBV) and highlight the importance for cooperatives of fostering an entrepreneurial culture, enhancing knowledge-sharing practices, and embedding innovation within strategic decision-making.